2014
DOI: 10.1152/ajpendo.00007.2014
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells respond to hyperglycemia by increasing the LPL transporter GPIHBP1

Abstract: In diabetes, when glucose uptake and oxidation are impaired, the heart is compelled to use fatty acid (FA) almost exclusively for ATP. The vascular content of lipoprotein lipase (LPL), the rate-limiting enzyme that determines circulating triglyceride clearance, is largely responsible for this FA delivery and increases following diabetes. Glycosylphosphatidylinositol-anchored high-density lipoprotein-binding protein [GPIHBP1; a protein expressed abundantly in the heart in endothelial cells (EC)] collects LPL fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Recently, studies have demonstrated that Sdc1 and HPSE are important endogenous regulators of energy balance and nutrient metabolism. HPSE overexpression and subsequent HS chains cleavage would not only cause diarrhoea, reduce reflex hyperphagia and food intake 2628, but also alter lipoprotein lipase and clearance of triglyceride 29,30. These emphasize yet again the diverse functions of Sdc1 and HPSE, and suggest their pathological effects of Sdc1/HPSE imbalance on systemic and intestinal homoeostasis under HG condition.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, studies have demonstrated that Sdc1 and HPSE are important endogenous regulators of energy balance and nutrient metabolism. HPSE overexpression and subsequent HS chains cleavage would not only cause diarrhoea, reduce reflex hyperphagia and food intake 2628, but also alter lipoprotein lipase and clearance of triglyceride 29,30. These emphasize yet again the diverse functions of Sdc1 and HPSE, and suggest their pathological effects of Sdc1/HPSE imbalance on systemic and intestinal homoeostasis under HG condition.…”
Section: Discussionmentioning
confidence: 87%
“…1 Given that the molar concentration of FA in lipoprotein-triglyceride is ≈10-fold greater than albumin-bound circulating FA, 5 LPL-mediated hydrolysis of circulating triglyceride is suggested to be the dominant source of FA for cardiac utilization during diabetes mellitus. 30 Previously, we have reported a robust augmentation in coronary LPL activity after acute moderate diabetes mellitus and linked this observation to an increased expression of EC GPIHBP1, 19 the transporter that transfers LPL from the basolateral to the apical (luminal) side of EC where the enzyme is functional. 9 Figure 5.…”
Section: Discussionmentioning
confidence: 98%
“…19 To mimic in vivo hyperglycemia, rat aortic ECs were exposed to high glucose. Interestingly, high glucose increased GPIHBP1 mRNA ( Figure 1A, left) and protein ( Figure 1A, right panel) expression within 12 hours.…”
Section: High Glucose Alters the Expression Of Endothelial Gpihbp1mentioning
confidence: 99%
See 2 more Smart Citations